Wave Energy: Boats on Waves Can Be a Source of Clean Energy - Moniruzzaman, Md. (European Journal of Applied Sciences, 2023)
The energy of ocean waves across a large part of the earth is inexhaustible. The whole world will benefit if this endless energy can be used in an easy way. The coastal countries will easily be able to meet their own energy needs. The purpose of this article is to use the infinite energy of the ocean wave in a simple way, i.e., a method of efficient use of wave energy. The paper starts by discussing specifically about pitch motion of a boat caused by waves. Afterward with a graphical presentation discussed about the method of using the force from pitch-movement of the boat. Finally, the conclusion states the possibilities, disadvantages and advantages.